MANAJEMEN PENDIDIKAN AL QUR’AN BERBASIS MASJID DALAM RAMADHAN KAMP (Study Kasus Masjid Nurul Huda Tarebung Kecamatan Gayam Sumenep) - Hartono Hartono (Menara Tebuireng, 2020)
The purpose of this research and community service is to provide understanding of the Qur'an and religious knowledge through instant Islamic boarding schools. The method used in this activity is Islamic boarding school-based religious learning in collaboration with mosque youth. Pesantren-based education has existed since the Prophet Muhammad "migrated" to Medina and his friends. The development of Islam cannot be separated from education and scientific assemblies that were directly fostered by the Prophet Muhammad four centuries ago. They always apply the knowledge they get and then teach it back to people in need. Some of them occupy the terrace space of the mosque and learn full time from the Prophet Muhammad about all the sayings, behavior and provisions or "takrir" of the Prophet Muhammad. The benefits that will be achieved, provide an instant understanding of the pesantren education model in the community through Romadhan camp. By introducing Islam as a whole to the community, it is hoped that Islam will not only be used as a dogma, let alone sensitivity for certain purposes. The implementation of the management of the Ramadan camp involves the community to enter their lives and teach Islam without having to patronize.